Development of an antimicrobial compound with silver nanoparticles synthesized from rosemary (rosmarinus officinalis) leaf extract, to be applied on fruits - Alvarado Aguilar, Marina Chanena; Arias Ortiz, Jason David; Palma Holguín, Marcos Ítalo (Ingeniería Química y Desarrollo, 2023)
This research aims the study of nanotechnology taking advance the natural resources of Ecuador. By using a plant to get nanoparticles friendlier with nature. It was used as a reducing agent obtained from rosemary leaves (Rosmarinus Officinalis) which facilitated the formation of nanoparticles without residues of toxic contaminants. The (AgNPs) were characterized by UV-VIS spectroscopy presenting an absorption in the range 400-418 nm, which corresponds to the surface plasmon resonance of the (AgNPs), also scanning electron microscopy (SEM) was used to determine the size and morphology of the (AgNPs) determining a spherical shape of 10 nm in diameter. It was verified through strains of E. coli, S. aureus and B. subtilis, the inhibitory activity producing halos of approximately 3.2 cm in diameter product of the (AgNPs) synthesized. Therefore, nanoparticles were applied to a traditional fruit (apple), a natural preservative (beeswax) was incorporated together with the (AgNPs). It caused efficient results proving its antimicrobial effect and maintaining its initial characteristics, concluding that the nanoparticles in this research are very high, due to their dimensions, inhibitory effect and excellent power in food preservation.
Keywords: Silver nanoparticles; reducing agent; green synthesis; activity antimicrobial; Rosmarinus officinalis